2018
DOI: 10.1016/j.spen.2018.05.003
|View full text |Cite
|
Sign up to set email alerts
|

Fetal Cerebrovascular Maturation: Effects of Hypoxia

Abstract: The human cerebral vasculature originates in the fourth week of gestation and continues to expand and diversify well into the first few years of postnatal life. A key feature of this growth is smooth muscle differentiation, whereby smooth muscle cells within cerebral arteries transform from migratory to proliferative to synthetic and finally to contractile phenotypes. These phenotypic transformations can be reversed by pathophysiological perturbations such as hypoxia, which causes loss of contractile capacity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 191 publications
(218 reference statements)
2
12
0
Order By: Relevance
“…Consistent with previous studies [ 35 , 37 ], neonatal hypoxic ischemia significantly shifted the phenotype of cerebrovascular smooth muscle ( Figure 4 B,D). In pups programmed by MUN, mild HI insult promoted contractile differentiation, as indicated by a rightward shift in pixel distributions for αActin colocalization that was most prominent with NM-MHC, but was also significant with SM-MHC ( Figure 4 B,D).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Consistent with previous studies [ 35 , 37 ], neonatal hypoxic ischemia significantly shifted the phenotype of cerebrovascular smooth muscle ( Figure 4 B,D). In pups programmed by MUN, mild HI insult promoted contractile differentiation, as indicated by a rightward shift in pixel distributions for αActin colocalization that was most prominent with NM-MHC, but was also significant with SM-MHC ( Figure 4 B,D).…”
Section: Discussionsupporting
confidence: 92%
“…Specifically, these studies have demonstrated that the phenotype of vascular smooth muscle, as indicated by differential expression of contractile proteins such as smooth muscle αactin and myosin heavy chain isoforms [ 33 , 34 ], can be potently modulated by fetal stress [ 35 , 36 ]. Correspondingly, changes in smooth muscle phenotype in response to the cardiovascular stresses imposed by hypoxia and ischemia, can alter both resting myogenic vascular tone and contractile responses induced by depolarizing stimuli, contractile agonists, and vasodilators [ 37 , 38 ]. A majority of studies of how fetal programming influences postnatal vascular structure and function have focused on mesenteric, renal and femoral arteries and have revealed attenuation of angiogenesis [ 27 ], reduced contractile responses to phenylephrine and norepinephrine [ 39 ], and reduced vasodilatory responses to acetylcholine, bradykinin, sodium nitroprusside, and presumably nitric oxide [ 40 ].…”
Section: Introductionmentioning
confidence: 99%
“…If the cerebral resistance continuously rises, a loss of autoregulation of the cerebral blood flow occurs and reverse flow begins. 16,18 The bleeding volume from intracranial hemorrhage causes increased intracranial pressure which interferes with the normal cerebral blood flow and the resistance in turn leads to reversed end-diastolic flow of the MCA. 15 In congenital hydrocephalus, excessive accumulation of cerebrospinal fluid also causes increased intracranial pressure that leads to reversed flow of the MCA.…”
Section: Discussionmentioning
confidence: 99%
“…Although not based specifically on the intracerebral capillaries associated with the NVU, these results nonetheless reinforce the notion that vascular responses to chronic hypoxia differ between the perinatal and adult brain. Via effects on contractile mechanisms and receptor affinities, chronic hypoxia attenuates cerebral arterial responses to vasoactive stimuli, impeding cerebrovascular homeostatic maintenance (Pearce, 2018). Chronic hypoxia has also been linked to alterations in sympathetic perivascular innervation, causing changes in cerebrovascular smooth muscle cell differentiation, and subsequently in vascular contractility and functioning (Adeoye et al, 2015;Pearce, 2018).…”
Section: Chronic Hypoxiamentioning
confidence: 99%
“…Via effects on contractile mechanisms and receptor affinities, chronic hypoxia attenuates cerebral arterial responses to vasoactive stimuli, impeding cerebrovascular homeostatic maintenance (Pearce, 2018). Chronic hypoxia has also been linked to alterations in sympathetic perivascular innervation, causing changes in cerebrovascular smooth muscle cell differentiation, and subsequently in vascular contractility and functioning (Adeoye et al, 2015;Pearce, 2018). Fetal cerebral vasculature also undergoes remodeling in response to in utero chronic hypoxia.…”
Section: Chronic Hypoxiamentioning
confidence: 99%